A wilful ward - Lamb, Ruth, 1829-1916 (Salt Lake City, UT : Project Gutenberg, 2023)
"A Wilful Ward" by Ruth Lamb is a novel written in the late 19th century. The story introduces Kathleen Mountford, a young heiress who grapples with strict social expectations and the limitations imposed by her late father, particularly regarding her participation in the local hunting meets. Through her conversations with her aunt and reflection on her mother's tragic past, the novel explores themes of freedom, duty, and the complexities of love and desire. The opening of the book sets the scene on a rainy November morning, as Kathleen expresses her disappointment over not being able to ride in the highly anticipated Hollingsby Hunt. Her aunt, Mrs. Ellicott, advocates for compassion towards all creatures affected by hunting, including foxes, while Kathleen demonstrates a mixture of youthful exuberance and rebellious spirit, longing to break free from her restrictions. As Kathleen prepares for a carriage ride to observe the event, there is a palpable tension surrounding her feelings for Captain Jack Torrance, a charming yet controversial figure in her life. This tension reveals Kathleen's inner conflict between her father's legacy and her desire for independence, setting the stage for the emotional complexities to come. (This is an automatically generated summary.)
Release date is 2023-06-27
Keywords: Conduct of life -- Juvenile fiction; England -- Juvenile fiction; Guardian and ward -- Juvenile fiction; Mate selection -- Juvenile fiction; Spouses -- Juvenile fiction